From the Molecular Structure to Spectroscopic and Material Properties: Computational Investigation of a Bent‐Core Nematic Liquid Crystal. Issue 7 (27th January 2014) - Greco, Cristina; Marini, Alberto; Frezza, Elisa; Ferrarini, Alberta
Abstract We present a computational investigation of the nematic phase of the bent‐core liquid crystal A131. We use an integrated approach that bridges density functional theory calculations of molecular geometry and torsional potentials to elastic properties through the molecular conformational and orientational distribution function. This unique capability to simultaneously access different length scales enables us to consistently describe molecular and material properties. We can reassign 13C NMR chemical shifts and analyze the dependence of phase properties on molecular shape. Focusing on the elastic constants we can draw some general conclusions on the unconventional behavior of bent‐core nematics and highlight the crucial role of a properly‐bent shape.